Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap KinerjaKaryawan PT. BTPN Syariah, Tbk. Sukabumi - Siti Hartinah (Universitas Linggabuana PGRI Sukabumi, 2020)
This research was conducted to prove the influence of the work environment and discipline on the performance of employees of PT. BTPN Syariah, Tbk Sukabumi during the Covid-19 pandemic, both independently and simultaneously. Researchers use statistical methods, determination and multiple linear regression with an associative approach according to its purpose. Where the sampling technique uses a census technique where all members of the population are taken as a sample of 50 people. The results of the research by means of regression analysis proved that there is a good influence between work environment and work discipline on the performance of employees of PT. BTPN Syariah, Tbk Sukabumi. and Coefficient of Determination there is a simultaneous influence of Work Environment and Work Discipline on Employee performance.